2016
DOI: 10.1111/fog.12192
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on the spatio‐temporal patterns of abundance and distribution of Sardina pilchardus and sardinella off the Mauritanian coast (North‐West Africa)

Abstract: From 1998 to 2011, the effects of environmental conditions on the spatial and temporal trends of sardine and sardinella catch rates in the Mauritanian waters were investigated using generalized additive models. Two models were used: a global model and an oceanographic model. The global models explained more of the variability in catch rates (60.4% for sardine and 40% for sardinella) than the oceanographic models (42% for sardine and 32.4% for sardinella). Both species showed clear and inverse seasonal variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 69 publications
8
31
0
Order By: Relevance
“…Conversely, the peak of abundance during the autumn might be due to the convergence of S. aurita , which continue to migrate from South to North (where the upwelling intensity was high last winter) with those in Mauritania that are beginning their Southward migration. Similar bimodal patterns were also found for other fish species such as octopus, sardine, shrimps and the whiter grouper, or “thiof” in the local name ( Epinephelus aeneus ) in NW Africa (Cury & Roy, ; Bacha, Jeyid et al., ; Bacha, Jehid et al., ). These authors suggested that the regional upwelling dynamics and local environmental effects might influence the migration of these species, i.e., the simultaneous relaxation and trigger of the coastal upwelling off Mauritania and Senegal, respectively.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Conversely, the peak of abundance during the autumn might be due to the convergence of S. aurita , which continue to migrate from South to North (where the upwelling intensity was high last winter) with those in Mauritania that are beginning their Southward migration. Similar bimodal patterns were also found for other fish species such as octopus, sardine, shrimps and the whiter grouper, or “thiof” in the local name ( Epinephelus aeneus ) in NW Africa (Cury & Roy, ; Bacha, Jeyid et al., ; Bacha, Jehid et al., ). These authors suggested that the regional upwelling dynamics and local environmental effects might influence the migration of these species, i.e., the simultaneous relaxation and trigger of the coastal upwelling off Mauritania and Senegal, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…The recent work by Bacha, Jeyid et al. (), Bacha, Jehid, Vantrepotte, Dessailly, and Amara () clearly indicated that the Mediterranean Sea and Atlantic Ocean S. aurita populations are distinct. Unlike the genetic study conducted off NW Africa (Chikhi, Agnèse, & Bonhomme, ), the otolith shape of S. aurita suggests the existence of isolated groups of fish.…”
Section: Introductionmentioning
confidence: 93%
“…This matches well with the modern latitudinal trends in upwelling in Mauritanian waters. The upwelling intensity is high and quasipermanent in the north, with a marked decrease toward southern Mauritania, where the seasonality is much more developed with the highest intensities between November and February (Bacha et al, ). In summer and autumn southern Mauritania comes under the influence of the West African Monsoon which reverses the flow direction along the coast by establishing the northward flowing Mauritania Current, suppressing upwelling (Kuhnert & Mulitza, ).…”
Section: Discussionmentioning
confidence: 99%
“…Monthly data concerning five environmental variables often applied to investigate relationships between fish abundance and environmental conditions (Bacha et al., ; Cury & Roy, ; Klemas, ; Thiaw et al., ) were used in our study: sea surface temperature (SST, in °C), chlorophyll‐ a concentration (Chl‐ a, in mg/m 3 ), wind‐induced turbulence (WTI, in m 3 /s 3 ) and a Coastal Upwelling Index (CUI, in m 3 /s 3 per meter of coast) deduced from wind data and North Atlantic Oscillation index (NAO). Except NAO, all variables were averaged from the coast to the 200 m isobaths, i.e., over almost all the Senegalese sardinella habitat, the continental shelf from 12 to 17°N (Figure ).…”
Section: Methodsmentioning
confidence: 99%